2020
DOI: 10.48550/arxiv.2009.04008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying the Effects of COVID-19 on Mental Health Support Forums

Abstract: The COVID-19 pandemic, like many of the disease outbreaks that have preceded it, is likely to have a profound effect on mental health. Understanding its impact can inform strategies for mitigating negative consequences. In this work, we seek to better understand the effects of COVID-19 on mental health by examining discussions within mental health support communities on Reddit. First, we quantify the rate at which COVID-19 is discussed in each community, or subreddit, in order to understand levels of preoccupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Text data from several individuals on social media, hospitality feedback from the patients on the treatment given to them, and forums such as blogs provide useful information about different COVID-19 related aspects. The mental health support communities on Reddit are analysed in [95], to understand the effects of COVID-19 on the mental health of society. It is observed that the posts on this community forum per day have increased specifically in the subreddits of Anxiety and SuicideWatch, however, decrease in the subreddit of depression during the pandemic period.…”
Section: Text Analysismentioning
confidence: 99%
“…Text data from several individuals on social media, hospitality feedback from the patients on the treatment given to them, and forums such as blogs provide useful information about different COVID-19 related aspects. The mental health support communities on Reddit are analysed in [95], to understand the effects of COVID-19 on the mental health of society. It is observed that the posts on this community forum per day have increased specifically in the subreddits of Anxiety and SuicideWatch, however, decrease in the subreddit of depression during the pandemic period.…”
Section: Text Analysismentioning
confidence: 99%